UJI IDENTIFIKASI BAKTERI PATOGEN PADA SUNGAI KALILO KECAMATAN BANYUWANGI: Identification Test of Pathogenic Bacteria in the Kalilo River, Banyuwangi District - Arini, Vhita Syukrya (Program Studi Biologi, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas PGRI Banyuwangi, Jalan Ikan Tongkol No 01, Telp (0333) 421593, 428592 Banyuwangi 68416, 2025)
Kalilo River is one of the main rivers that flows through densely populated areas in Banyuwangi District. Various community activities such as bathing, washing, waste disposal, and defecation directly into the river have contributed to the decline in water quality. These conditions increase the potential for microbiological contamination, particularly the presence of pathogenic bacteria that can harm public health. This study aims to identify pathogenic bacterial species present in the Kalilo River as indicators of pollution. Water samples were collected from a single location and tested at the Regional Health Laboratory using NA, SSA, and EMB media. Gram staining was conducted to observe bacterial morphology. The results revealed the presence of two pathogenic bacteria, Escherichia coli and Shigella sp., indicating fecal contamination. These findings suggest a significant health risk if the water is used without treatment. Proper domestic waste management and community environmental education are needed to address this issue.